Two cases of spontaneous cervical epidural hematoma without back or neck pain in elderly Japanese men. Issue 2 (24th October 2017) - Hongo, Takashi; Iseda, Kenichi; Tsuchiya, Midori; Inaba, Mototaka; Nozaki, Satoshi; Takahashi, Kenji; Nakajima, Masaaki; Fujiwara, Toshifumi
Abstract : Cases: Spontaneous spinal epidural hematoma (SSEH) is an uncommon disease. Most SSEH cases involve back and/or neck pain. We report the cases of two men who experienced SSEH with dysstasia but without back or neck pain. Outcomes: This study presents two cases involving elderly Japanese men who visited an emergency department because of sudden dysstasia without back or neck pain. The results of the neurological examinations revealed ataxic gait. Cervical spinal epidural hematomas were observed by computed tomography and magnetic resonance imaging. One patient underwent hematoma removal and decompression by corpectomy, whereas the other patient received conservative treatment and observation. The patients were discharged without sequelae. Conclusion: Spinal epidural hematomas are difficult to diagnose, and a delayed diagnosis can adversely affect the patient's quality of life. These hematomas should be considered in the differential diagnosis of cerebrovascular diseases. Abstract : This figure shows spinal epidural hematoma. We performed hematoma removal and decompression by corpectomy from the front of C3‐5.